Orientasi Pasar, Moderasi Dinamika Lingkungan pada Efek Strategi Bersaing terhadap Kinerja (Studi pada Industri Kecil Menengah Tenun di Sulawesi Tenggara) - .., Rosnawintang; Salim, Ubud; Thoyib, Armanu; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2012)
The objective of research is to measure and to analyze the effect of market orientation on competing strategy, competing strategy on performance, market orientation on performance, and environmental dynamic moderation in the competing strategy on performance at weaving small-middle industries at Southeast Sulawesi. Research object is that the weaving small-middle industries (SMI's) at Southeast Sulawesi. Data type is primary data. The population of the weaving SMI's is 219 units. Sampling technique is Saturation Sampling. There are 202 units of questionnaire but only 2 are unused. Therefore, the population to analyze is 200 units spread throughout five districts/towns at Southeast Sulawesi. The analysis tool is Structural Equation Model with Amos 16 Program. The findings of the study show that increasing performance of the SMIs in Southeast Sulawesi is done directly through market orientation effectiveness and indirectly done through proper competitive strategy application. The environment dynamics strengthens the appropriateness of competitive strategy to increase the performance of the weaving SMIs in Southeast Sulawesi. The market effectiveness of market orientation done through customers' orientation with competitive strategy through product differentiation has increased the performance of the weaving SMIs. The appropriate application of competitive strategy suitable with environment dynamic through the intensity of competition encourages the increase of performance at the market share extension of the weaving SMIs in Southeast Sulawesi.